DOI: 10.11606/t.8.2008.tde-19122008-095822
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos impactos ambientais de plantações de eucalipto no Cerrado com base na análise comparativa do ciclo hidrológico e da sustentabilidade da paisagem em duas bacias de segunda ordem

Abstract: Fidalgo Garcez, pela simpatia e competência dispensadas, e a todos os funcionários da FFLCH/USP. Aos colaboradores do Laboratório de Geomorfologia, do Curso de Geografia da FFLCH/USP. À Profª Cleide Rodrigues e ao Prof. Emerson Galvani pelas contribuições na banca de qualificação. Ao Serviço de Atendimento Social, por disponibilizar o alojamento temporário do Conjunto Residencial da USP nos momentos de permanência na Universidade. A ESALQ/USP por oportunizar, através do Mestrado, as bases para realização deste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 9 publications
1
10
0
3
Order By: Relevance
“…Farley et al (2008) observed, in paired water sources in the Pampa biome in Argentina and Uruguay, mean values of 7.2 and 6.5, respectively, for grassland uses and planting eucalyptus. Mosca (2008) observed pH values between 6 and 7 in a watershed where eucalyptus had been planted in the Cerrado, without much variation during the dry and rainy periods, according to what has been observed in the present study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Farley et al (2008) observed, in paired water sources in the Pampa biome in Argentina and Uruguay, mean values of 7.2 and 6.5, respectively, for grassland uses and planting eucalyptus. Mosca (2008) observed pH values between 6 and 7 in a watershed where eucalyptus had been planted in the Cerrado, without much variation during the dry and rainy periods, according to what has been observed in the present study.…”
Section: Resultssupporting
confidence: 90%
“…The elevated mean found in EW explains the increased pH found in the area of study. According to Mosca (2008) the capacity to neutralize acids in an aqueous system depends on some compounds such as bicarbonates, carbonates and hydroxides.…”
Section: Resultsmentioning
confidence: 99%
“…The may be related to the presence of extensive livestock waste that through decomposition of organic material provide conditions for the reduction of the pH (Table 1), as noted by Mosca (2008), so VF4 may be characterized as an "anthropic" factor. Messias (2008) states that the pH can be considered one of the most important and complex environmental variables to interpret, due to the numerous factors that influence the environment, and such complexity is related to diffuse sources of pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Ao longo das décadas, diversos incentivos foram concedidos pelos diferentes governos e, no ano 2000, com a criação do Programa Nacional de Florestas, novamente são estabelecidas políticas governamentais para o aumento das áreas plantadas. Tais estratégias estariam alinhadas com a desejável fixação do carbono atmosférico, de conformidade com as exigências globais impostas para a diminuição da emissão de carbono e de gases do efeito estufa (MOSCA, 2008).…”
unclassified